Strategic Change Management for Behavioral Transformation At Batik Pringmas Using Lewin’s Model in Digital Marketing Adoption - Kensha Putri Widyasari; Achmad Sudjadi; Siti Zulaikha Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Digital transformation presents both opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs) in adapting their organizational behavior and marketing practices. Batik Pringmas, a traditional batik MSME located in Banyumas Regency, is currently facing difficulties in transitioning to digital marketing due to low digital literacy, limited human resources, and a reliance on conventional methods. This study aims to develop a strategic change management framework to support behavioral transformation within the organization, using Kurt Lewin’s three-stage model: unfreezing, changing, and refreezing. A qualitative research method was employed, incorporating observation, semi-structured interviews, and documentation. The findings show that the unfreezing phase involves raising awareness about the urgency of digital adoption; the changing phase includes training on digital tools, utilizing social media platforms, and integrating marketplaces; and the refreezing phase involves reinforcing digital habits in daily operations. The proposed strategy not only facilitates behavioral change but also ensures that the organization can sustain digital practices in the long term. Keywords: Change Management, Behavioral Transformation, Batik Pringmas, Lewin’s Model, Digital Marketing